Role of Extracellular Carbonic Anhydrase in Dissolved Inorganic Carbon Uptake in Alkaliphilic Phototrophic Biofilm - Li, Tong; Sharp, Christine E.; Ataeian, Maryam; Strous, Marc; de Beer, Dirk (Frontiers in Microbiology, 2018)
Alkaline Soda Lakes are extremely productive ecosystems, due to their high bicarbonate concentrations. Here, we studied the dynamics of the carbonate buffer system, in particular, the role of extracellular carbonic anhydrase (eCA) of an alkaliphilic phototrophic biofilm composed of bacteria enriched from soda lake benthic mats. By using measurements with microsensors and membrane inlet mass spectrometry, combined with mathematical modeling, we show how eCA controls bicarbonate uptake. In our experiments, the activity of eCA varied 4-fold, and was controlled by the bicarbonate concentration during growth: a higher bicarbonate concentration led to lower eCA activity. Inhibition of eCA decreased both the net and the gross photosynthetic productivities of the investigated biofilms. After eCA inhibition, the efflux of carbon dioxide (CO2) from the biofilms increased 2- to 4-fold. This could be explained by the conversion of CO2, leaking from cyanobacterial cells, by eCA, to bicarbonate. Bicarbonate is then taken up again by the cyanobacteria. In suspensions, eCA reduced the CO2 leakage to the bulk medium from 90% to 50%. In biofilms cultivated at low bicarbonate concentration ( 0.13 mM), the oxygen production was reduced by a similar ratio upon eCA inhibition. The role of eCA in biofilms was much less significant as CO2 loss to the medium is reduced due to mass transfer resistance.